Florística e fitogeografia das samambaias e licófitas de fragmento de Mata Atlântica na Serra da Jibóia, Santa Teresinha, Bahia, Brasil - Macedo, Taís Soares (2011)
(Floristic and phytogeography of ferns and lycophytes of Atlantic Forest fragment in the Serra da Jibóia, Santa Teresinha, Bahia State, Brazil). Studies in Bahia State involving ferns and lycophytes are still few, so there is a gap in knowledge of species, especially those occurring in the Atlantic Forest. Serra da Jibóia, located in the Municipality of Santa Teresinha, Bahia State, Brazil, in the geographic coordinates 12º51'S and 39º28'W, presents several vegetation formations: areas of caatinga in the base, humid forest on the slope and in the top, on gneiss-granite outcrop, a ‘campo rupestre’ (grasslands with rocks) vegetation. The area is considered of extreme biological importance and priority for biodiversity conservation of Brazilian Atlantic Forest. This study aimed to provide a floristic and phytogeographical survey of ferns and lycophytes of the fragment of Atlantic Forest in the Serra da Jibóia, trying to understand their floristics relations with other vegetation formations in the country and contribute to the knowledge of the vascular flora of the region and complement the knowledge about the Atlantic Forest. Monthly collections during the years 2009 and 2010 were made, following the usual techniques. Materials from the collections of herbaria ALCB, HRB and HUEFS were also reviewed. All material collected is deposited in HUEFS. 97 species in 51 genera and 22 families were found. Six species are new records for the Northeast region and three for the Bahia State. The most representative families were Dryopteridaceae (17 spp.), Polypodiaceae (16 spp.), Pteridaceae (12 spp.) and Hymenophyllaceae (10 spp.). Most species occurs as epiphyte (43%), 39% terrestrial, 4% lythophyte, 3% hemiepiphyte and 8% with more than one type of habit. Identification keys, geographic distribution and important taxonomic comments are presented. The analysis of similarity to other 26 areas, representing different vegetations formations of the country, showed that the flora of ferns and lycophytes of the Serra da Jibóia is related to the south of Bahia and Southeast Brazil.